Genes vs environment in inflammatory bowel disease: an update. (3rd October 2022) - Dipasquale, Valeria; Romano, Claudio
ABSTRACT: Introduction: Inflammatory bowel diseases (IBDs) are known to be caused by a combination of genetic and environmental factors that vary in their influence on the development of the disease. Environmental exposures seem to influence IBD susceptibility, whereas genetic background is thought to modulate the impact of the environment on disease course and phenotype. Areas covered: A broad review of the involvement of genes and the environment in IBD pathogenesis was performed, and information regarding the main genetic and environmental factors – categorized into lifestyle factors, drugs, diet, and microbes – was updated. Monogenic very early onset IBD (VEO-IBD) was also discussed. Expert opinion: In the upcoming years, better understanding of gene-environment interactions will contribute to the possibility of a better prediction of disease course, response to therapy, and therapy-related adverse events with the final goal of personalized and more efficient patient management.